A Regional Economic History of Thailand - Ouyyanont, Porphant ([S.l.] : ISEAS - Yusof Ishak Institute, 2017)
This book presents an economic history of Bangkok, the Central Region, the North, the South, and Northeastern Regions from the signing of the Bowring Treaty in 1855 to the present. Most research has focused on Bangkok as the centre of change affecting other regions and has neglected other regions that had an influence on Bangkok. This book however looks at the changes not only in Bangkok, but also in the other regions, and emphasizes the ways in which Bangkok had an impact on the other regions, and how changes in the other regions affected Bangkok. It also looks, in turn, at each of the principal regions, and concentrate on the long-term economic and social changes and the various forces which promoted the changes
Regional Economic History of Thailand -- Contents -- Preface -- Acknowledgements -- Glossary -- Abbreviations -- Siamese Money and Weight -- Reigns of the Kings of the Chakri Dynasty -- 1. Introduction -- 2. Bangkok -- 3. Central Region -- 4. The North -- 5. The South -- 6. The Northeast -- 7. Conclusion -- Selected Bibliography -- Index -- About the Author.
Includes bibliographical references and index.
Keywords: Economic history